252 Efficiency of Utilization of Methionine for Weight Gain in Weaning Pigs is not Affected by Methionine Source: A Meta-Analysis. (21st September 2022) - Remus, Aline; Souza, Vinicius; Batonon-Alavo, Dolores I; Rouffineau, Friedrich; Kebreab, Ermias; Pomar, Candido
Abstract: Methionine is an essential dietary amino acid that can be supplied in different chemical forms: DL-methionine, L-methionine, and OH-methionine. It has been hypothesized that L-methionine might be used with greater efficacy for average daily gain (ADG) in weaning pigs due to their decreased enzymatic capacity to convert the other methionine forms. This study aimed to compare DL-methionine, L-methionine, and OH-methionine efficiency of utilization for ADG in weaned pigs through meta-analysis.The systematic review resulted in 2, 167 papers screened for the title and abstract, with 24 papers meeting the inclusion criteria. The ADG was regressed as a function of the standardized ileal digestible (SID) methionine intake (Meti ). The study was used as a random intercept, and regressions were weighted by the square root of the number of observations. Non-linear models were used to determine the Meti requirements. The average Meti requirement for pigs of 5 to 25 kg body weight (BW) was 2.09 g/d. The slopes of linear mixed-effects regression models were compared for the different methionine sources. Average initial BW was 7.99 (DL-methionine), 8.82 (L-methionine), and 7.06 kg (OH-methionine). Meti was 1.5 g/d for all sources whereas SID cysteine intake was 1.90, 2.23, and 1.93 g/d, for DL-methionine, L-methionine, and OH-methionine, respectively . Increase in Meti below the estimated requirement linearly increased ADG (ADG = 107 + 138 × Meti ; P < 0.01). No difference between the slopes of methionine sources was observed, rejecting the hypothesis that L-methionine is used with greater efficiency in weaned pigs. Pigs receiving DL-methionine, L-methionine, and OH-methionine presented an estimated ADG of 319, 317, and 311 (SE = 19, 25 and, 26, respectively) g/d, respectively. In conclusion, methionine efficiency of utilization for ADG in post-weaned pigs is not affected by methionine sources.